MODERATING EFFECT OF AUDIT QUALITY ON AUDIT COMMITTEE CHARACTERISTICS, OWNERSHIP STRUCTURE AND PERFORMANCE OF LISTED CONSUMER GOODS COMPANIES IN NIGERIA - Iliya, Ayuba; Abubakar, Abdulkadir; Shagari, Shamsudeen Ladan (Kashere Journal of Management Sciences, 2024)
This study examines the moderating effect of audit quality on the relationship between audit committee characteristics, ownership structure and performance of listed consumer goods companies in Nigeria. The study adopted ex-post facto and correlational research design and collected data using secondary method from published annual reports of the selected companies and the Nigerian Exchange Group. The population of this study was 21 listed consumer goods companies in Nigeria where 11 were considered as the sample size. The data gathered were analyzed using descriptive and inferential statistics such as multiple regression with the help of STATA version 14. The study found that audit committee meetings and audit committee size have a negative relationship with performance of consumer goods companies while block holders and institutional ownership have a positive relationship with performance. Whereas, the result of the moderating relationship revealed that audit quality moderate the relationship between audit committee meeting, audit committee size and block holders’ ownership while no moderation was found on institutional ownership. It was recommended that additional shares should be allotted to institutional investors since they tend to guard against their investment. The study also recommends that regulatory bodies in Nigeria must put more effort on improving the effectiveness of corporate governance mechanisms with specific focus on the effect of concentrated ownership structure and audit quality.